Preparation of Biopolymeric Nanofiber Containing Silica and Antibiotic - A. Bagheri Pebdeni (Journal of Nanostructures, 2016)
The biocompatible and biodegradable polymer nanofiber with high potential for anti-bacterial coating are used for: multi-functional membranes, tissue engineering, wound dressings, drug delivery, artificial organs, vascular grafts and etc. Electrospinning nanofiber made of scaffolding due to characteristics such as high surface to volume ratio, high porosity and very fine pores are used for a wide range of applications. In this study, polymer composite nanofiber Silica/chitosan/poly (ethylene oxide) /cefepime antibiotic synthesis and antibacterial properties will be discussed. The optimum conditions for preparation of electrospun nanofiber were: voltage; 21 kV, feed rate; 0.5 mL/h, nozzle-collector distance; 10 cm, and chitosan/poly(ethylene oxide) weight ratio 90:10 and the volume ratio of chitosan/silica is 70:30.  The antibacterial activity of composite scaffolds were tested by agar plate method by two type bacteria including Escherichia coli and Staphylococcus aureus. With the addition of the silica to chitosan, the hybrid was more biodegradable and improves the mechanical properties of biopolymer.